A Genetically Encoded 19F NMR Probe for Tyrosine Phosphorylation1. Issue 14 (28th February 2013) - Li, Fahui; Shi, Pan; Li, Jiasong; Yang, Fan; Wang, Tianyuan; Zhang, Wei; Gao, Feng; Ding, Wei; Li, Dong; Li, Juan; Xiong, Ying; Sun, Jinpeng; et al.
<x xml:space="preserve">Abstract</x> Simple and selective: Tyrosine phosphorylation is a pivotal post‐translational modification which regulates the enzymatic activity, protein conformation, and protein–protein interactions. The highly efficient genetic incorporation of 3, 5‐difluorotyrosine (F2Y) in E. coli and the use of F2Y as a 19F NMR probe for the tyrosine phosphorylation are reported (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>